VALIDATED GRADIENT STABILITY INDICATING RP-HPLC METHOD FOR THE SIMULTANEOUS QUANTIFICATION OF 11 RELATED SUBSTANCES IN THE COMBINED DOSAGE FORMS OF LAMIVUDINE AND TENOFOVIR DISOPEOXIL FUMARATE - Babu, C.; Devanna, N.; Reddy, K. V.n. Suresh (International Journal of Applied Pharmaceutics, 2017)
Objective: Development of a stability-indicating reverse phase liquid chromatographic (RP-HPLC) method for the simultaneous quantification of 11 impurities in the combined dosage forms of lamivudine and tenofovir disoproxil fumarate drug substances. Methods: Efficient chromatographic separation of all analytes was achieved on a Waters X-terra RP18 column (150 x 4.6 mm, 3.5 mm) using mobile phase A (ammonium acetate buffer, pH adjusted to 5.0Â±0.05 with dilute orthophosphoric acid) and mobile phase B (mixture of methanol and ammonium acetate buffer in the ratio of 20:80) with the flow rate of 1.0 ml/min in gradient elution mode at 260 nm. Results: The method was validated in terms of the limit of detection, limit of quantification, linearity, accuracy, precision and robustness according to the international conference on harmonisation (ICH Q2R1). Regression analysis showed that the correlation coefficient (r2) is greater than 0.997 for individual active drug substances as well as their related substances. The method has proven very accurate (94.6 % to 108.2 % with % RSD not more than 4.9), highly precise (% RSD of the Intra-day and the inter-day study was not more than 8.9) and robust enough to deliver accurate results, when the chromatographic conditions were altered intentionally. Forced degradation studies were conducted in acidic, basic, thermal, photolytic, humid and peroxide stress conditions, where all the degradation peaks were monitored. Highest degradation of lamivudine was observed under oxidative stress condition and tenofovir was more susceptible to degradation under acidic and alkaline conditions. Conclusion: The present method is able to separate all the related compounds with each other and with the main drug substances with the resolution more than 2.0. The test solution was found to be stable in diluent up to 24 h. The mass balance of forced degradation of formulations, close to 99 %, made this method as a stability indicating method.